Travel as the Answer: Bodo Kirchhoff “Widerfahrnis” - Katinienė, Violeta (Literatūra, 2022)
Travels and the longing for afar have been and still are the source of inspiration for many authors. This article analyses Bodo Kirchoff’s short story “Widerfahrnis” (“Encounter”), which belongs to the genre of travel literature and extends the literary tradition of German authors to choose the theme of travel to Italy in their work (Johann Wolfgang von Goethe, Heinrich Heine, Thomas Mann, etc.). The short story raises the existential questions of longing for love, loneliness, confrontation with refugees, and moral and social aspects of relations with them. The article aims to reveal how the structures of experience described by the German phenomenologist Bernhard Waldenfels appear in the work of Bodo Kirchhoff. What happens to us does not happen without our involvement but goes beyond it. The experience begins not with the intentional gaze of the subject, but when someone (a stranger) touches us, encounters us, causes us to react and raises tension. Bernhard Waldenfels attributes the encounter to the realm of pathos, meaning to the realm of feelings. Response or the inevitable response to an encounter comes earlier than an understanding or an answer. Although the title of the short story is in the singular form, it reveals many encounters: a meeting of an older couple, a spontaneous trip to Italy, an encounter with a refugee girl and a refugee family, the birth of love and its loss.